2023
DOI: 10.1021/acs.inorgchem.3c00095
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Reaction-Directed Green Synthesis of CeO2–MnO2 Catalysts for Imine Production through Oxidative Coupling of Alcohols and Amines

Abstract: Direct oxidative coupling of alcohols with amines over cheap but efficient catalysts is a promising choice for imine formation. In this study, porous CeO2-MnO2 binary oxides were prepared via an interfacial reaction between Ce2(SO4)3 and KMnO4 at room temperature without any additives. The as-prepared porous CeO2–MnO2 catalyst has a higher fraction of Ce3+, Mn3+, and Mn4+ and contains larger surface area and more oxygen vacancies. During the oxidative coupling reaction of alcohol with amine to imine, the as-ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Controversial results have been published regarding the influence of aniline concentration in the benzyl alcohol oxidation over the ceria surface. Some authors observed a strong influence, , while others show a small or even a non-influence . The aniline concentration was changed from 0 to 2 mmol (0, 0.5, 1, and 2 mmol).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Controversial results have been published regarding the influence of aniline concentration in the benzyl alcohol oxidation over the ceria surface. Some authors observed a strong influence, , while others show a small or even a non-influence . The aniline concentration was changed from 0 to 2 mmol (0, 0.5, 1, and 2 mmol).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, manganese-based and ceria-based catalysts have been explored as alternatives to noble-metal catalysts. Reaction conditions can force cerium ions in ceria to be interconverted between Ce 4+ and Ce 3+ . This interconversion reversibly releases oxygen from the ceria structure and produces oxygen vacancies in the crystal lattice.…”
Section: Introductionmentioning
confidence: 99%
“…MnO x -based matrix oxides (MnO x -CM). Li et al 48 prepared porous CeO 2 -MnO 2 binary oxides by an interfacial reaction between Ce 2 (SO 4 ) 3 and KMnO 4 at room temperature without any additives (Fig. 3c).…”
Section: O Vacancy (Ov)mentioning
confidence: 99%
“…Li et al 48 reported the application of the CeO 2 –MnO 2 catalyst for imine synthesis. The results demonstrated a remarkable catalytic activity, with 98% conversion of benzyl alcohol and 97% selectivity of imine (Scheme 12).…”
Section: Sustainable Synthesis Of Value-added Chemicalsmentioning
confidence: 99%
“…Imines are important organic intermediates with CN bonds that are extensively used in the synthesis of agricultural resources, fine chemicals, pharmaceutical compounds, biologically active ingredients, and materials. , The traditional preparation method involves the condensation reaction of amines and perishable carbonyl compounds with the help of acidic catalysts and dehydrating agents to form imines . Recently, many different synthesis strategies have been developed, including self-coupling reaction of primary amine, , oxidative dehydrogenation reaction of secondary amine, and the cross-coupling reaction of alcohol and amine. , Due to the cheap and readily available substrates, as well the only byproduct, which is water, one-pot oxidative coupling of amines and alcohols is an ideal synthetic method. , Various homogeneous and heterogeneous catalysts including Pd, Au, Pt, Ru, Ni, Mn, Co, , and Cu have been developed in this synthesis system. In 2015, Tamura and Tomishige found that due to its unique Ce 4+ /Ce 3+ redox pair, cheap CeO 2 exhibited outstanding catalytic activity for this reaction .…”
Section: Introductionmentioning
confidence: 99%